The Trans-European Transport Corridors: Contribution to Economic Performances of European Regions - Miljković, Marko M; Jovanović Gavrilović, Biljana; Petrović Vujačić, Jelica (Industrija, 2018)
Previous empirical researches have mostly confirmed the existence of positive impact of transport infrastructure investments on economic growth of national economies. There are a very few researches carried out at the lower levels of territorial units, mostly at the levels of NUTS-1 or NUTS-2 statistical regions. The aim of this paper is to analyse economic effects of transport infrastructure development at even lower level of territorial units, i.e. at the level of NUTS-3 statistical regions. The paper compares economic performances of the TEN-T European regions characterized by developed core trans-European road and rail transport network, with economic performances of other regions without the core network. A significant difference in favour of the TEN-T regions was identified, both in the case of gross value added of the entire economy and gross value added of the manufacturing industry. No significant differences were identified in terms of the employment rate. On the other hand, the labour productivity is higher in the TEN-T regions, primarily in the manufacturing industry, as a direct consequence of reducing transport time and transport costs.